2020
DOI: 10.3390/ijms21020374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 15 BMI-Associated Polymorphisms, Reported for Europeans, across Ethnicities and Degrees of Amerindian Ancestry in Mexican Children

Abstract: In Mexico, the genetic mechanisms underlying childhood obesity are poorly known. We evaluated the effect of loci, known to be associated with childhood body mass index (BMI) in Europeans, in Mexican children from different ethnic groups. We performed linear and logistic analyses of BMI and obesity, respectively, in Mestizos and Amerindians (Seris, Yaquis and Nahuatl speakers) from Northern (n = 369) and Central Mexico (n = 8545). We used linear models to understand the effect of degree of Amerindian ancestry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…Among the urban communities and indigenous groups, there are different levels of westernized lifestyles [ 25 , 26 ]. In particular, the Yaqui group currently represents a population of 45,000 individuals divided into eight villages, who live in rural and urban communities, showing a high genetic and cultural mixture [ 10 , 27 , 28 ]. Currently, adult Yaquis are the most likely group to be overweight or obese among the populations in northern areas (87.6%) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the urban communities and indigenous groups, there are different levels of westernized lifestyles [ 25 , 26 ]. In particular, the Yaqui group currently represents a population of 45,000 individuals divided into eight villages, who live in rural and urban communities, showing a high genetic and cultural mixture [ 10 , 27 , 28 ]. Currently, adult Yaquis are the most likely group to be overweight or obese among the populations in northern areas (87.6%) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no straightforward explanation for why the AUC-ROCs outperform in Seris compared to the rest of the groups, but probably, the answer lies in a mixture of genetics, dietary patterns, and lifestyle. The Seri group is an isolated hunter-gatherer and fishing community in the desert of northwestern Mexico [ 31 ], with different Amerindian ancestry from the rest of the groups [ 10 , 11 ]. Seafood is an important part of the Seri diet [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A latest study also found that the LMX1B rs10733682 is associated with BMI in Pima Indian adults [20]. Another LMX1B polymorphism loci rs3829849 was found to be associated with obesity in Central Mexican children [21]. Furthermore, genetic variants associated with BMI may also influence eating behavior, and it has been shown that the LMX1B rs10733682 is nominally associated with satiety responsiveness [22].…”
Section: Introductionmentioning
confidence: 94%